1958
DOI: 10.1002/j.1551-8833.1958.tb20717.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Studies of Water Coagulation

Abstract: T H E importance of alum coagula-electrolytes commonly found in water, tion in removing colloidal impuri-have been the subject of many investities from water is well known. . Workers have found though much valuable experimental that good flocculation with both alum work has been done on the problems and ferric sulfate occurs within a relainvolved and although the techniques tively narrow pH range. Unfortufor coagulation with alum are well ad-nately, these results have also been vanced, the mechanisms have neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…He showed -80 A. P. BLACK & D. G. WILLEMS that, whereas practically all the iron is precipitated by NaOH from a O.OIM solution of ferric alum below pH 4.0, precipitation of aluminum by NaOH from a 0.005M solution of potassium alum does not approach completion until about pH 5.4. The pH values observed in this study indicate, therefore, that hydrolysis products of ferric sulfate were formed in both waters without the addition of any form of alklalinity, whereas with regard to alum, hydrolysis products were not formed without the addition of alkalinity in Water A but could and did form without added alkalinity in Water B. Pilipovich and others 8 was employed, and the pH was adjusted with HCt and Ca(OHh likewise reported that the hydrolysis products of alum are most effective in reducing or reversing the zeta potential of floc particles. Miller 11,12 showed that the hydrolysis products of both alum and ferric sulfate are basic sulfates of fairly uniform composition throughout the major part of the pH range within which hydrolysis takes place.…”
mentioning
confidence: 49%
“…He showed -80 A. P. BLACK & D. G. WILLEMS that, whereas practically all the iron is precipitated by NaOH from a O.OIM solution of ferric alum below pH 4.0, precipitation of aluminum by NaOH from a 0.005M solution of potassium alum does not approach completion until about pH 5.4. The pH values observed in this study indicate, therefore, that hydrolysis products of ferric sulfate were formed in both waters without the addition of any form of alklalinity, whereas with regard to alum, hydrolysis products were not formed without the addition of alkalinity in Water A but could and did form without added alkalinity in Water B. Pilipovich and others 8 was employed, and the pH was adjusted with HCt and Ca(OHh likewise reported that the hydrolysis products of alum are most effective in reducing or reversing the zeta potential of floc particles. Miller 11,12 showed that the hydrolysis products of both alum and ferric sulfate are basic sulfates of fairly uniform composition throughout the major part of the pH range within which hydrolysis takes place.…”
mentioning
confidence: 49%
“…To analyze factors which influence the dispersion and flocculation behavior of soil particles, many studies have so far been conducted. The factors considered to be important include organic matter (Visser and Caillier 1988;Piccolo and Mbagwu 1989), free oxides (Oades 1984;Goldberg 1989), electric charge of clays (Pilipovich et al 1958;Black and Sidney 1961), clay mineralogy (VelascoMolina et al 1971), exchangeable cation composition (Chiet al 1977;Emerson and Chi 1977), electrolyte concentration (Quirk and Schofield 1955), soil pH (Goldberg and Glaubig 1987), particle size distribution (Rengasamy et al 1984) and so on. However, since the characteristics of the soil samples investigated in these studies were different from place to place, care must be taken in the interpretation of the role of the factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although electrophoretic mobility was recognized by Reuss in 1809, it was not related to water or water treatment before 1928, when Mattson published his ground-breaking study.' Even then, it was not until Black [2][3][4][5][6] and associates published a series of papers beginning in 1958 that ZP in water treatment received the attention it deserved.…”
Section: Zeta Potentialmentioning
confidence: 99%